Cystic fibrosis and coeliac disease: Coexistence in two children. Issue 9 (September 1973) - Goodchild, Mary C.; Nelson, R.; Anderson, Charlotte M.
Abstract : Two children, unrelated, in whom cystic fibrosis had been diagnosed at the ages of 14 weeks and 10 months, respectively, were found subsequently to suffer from coeliac disease as well. Both children are responding well to dietary gluten withdrawal and to conventional treatment for cystic fibrosis. It is suggested that cystic fibrosis may predispose to the development of coeliac disease. Therefore, jejunal biopsy may be a useful investigation in the occasional child with cystic fibrosis, who presents with unusual features, and who fails to thrive as well as expected.